2020
DOI: 10.2174/1389200221666200719004035
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Disease States on Rituximab Pharmacokinetics

Abstract: Background: The anti-CD20 antibody rituximab, which promotes the selective depletion of CD20 positive B cells, was the first targeted therapy that was approved for the treatment of B-cell malignancies, and it is now widely prescribed in both malignant and non-malignant, immune-related diseases. However, the cause of its various clinical responses in certain diseases, have not been clearly elucidated. The variabilities in inter-individual pharmacokinetic and the emerging evidence of the relationships between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
1
11
1
Order By: Relevance
“… 9 The high variability of pharmacokinetics and thereby B-cell recovery times makes it difficult to define ideal vaccination timepoints and to predict immune responses to vaccines. 10 There is an urgent need for evidence-based recommendations for administration of SARS-CoV-2 vaccines in immunocompromised patients, since in the absence of randomised controlled trials, current recommendations to delay B-cell-depleting therapies are based on previous influenza vaccination studies 7 and emerging humoral data on immune responses to SARS-CoV-2 vaccines in immunocompromised patients. 11 , 12 , 13 , 14 , 15 , 16 An improved understanding of humoral and cell-mediated responses following vaccination against SARS-CoV-2 in patients treated with anti-CD20-depleting agents is a prerequisite for the development of individualised vaccination strategies for this population.…”
Section: Introductionmentioning
confidence: 99%
“… 9 The high variability of pharmacokinetics and thereby B-cell recovery times makes it difficult to define ideal vaccination timepoints and to predict immune responses to vaccines. 10 There is an urgent need for evidence-based recommendations for administration of SARS-CoV-2 vaccines in immunocompromised patients, since in the absence of randomised controlled trials, current recommendations to delay B-cell-depleting therapies are based on previous influenza vaccination studies 7 and emerging humoral data on immune responses to SARS-CoV-2 vaccines in immunocompromised patients. 11 , 12 , 13 , 14 , 15 , 16 An improved understanding of humoral and cell-mediated responses following vaccination against SARS-CoV-2 in patients treated with anti-CD20-depleting agents is a prerequisite for the development of individualised vaccination strategies for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all clinical studies in which rituximab serum levels have been evaluated have demonstrated that the observed large interindividual variability in rituximab serum levels could be related to the "target burden" (Cartron et al, 2007;Golay et al, 2013;Wang et al, 2020). It is not surprising that the baseline CD19 + lymphocyte count was found to be inversely correlated with the rituximab level, a higher concentration of rituximab would be needed to neutralize the high amount of circulating B cells in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of RTX in patients differs according to disease type and activity (57), with one of the most altered pharmacokinetic profiles having been described in MN patients during periods with high levels of non-selective proteinuria (11). Pharmacokinetic parameters described in different studies vary due both to the different diseases studied and the different pharmacokinetic models and analytical methods applied (10). Therefore, Bensalem et al used concentration-time data from 5 different studies and applied the same method to calculate RTX pharmacokinetic characteristics.…”
Section: The Pharmacokinetics Of Rituximab and The Covariates That In...mentioning
confidence: 99%
“…Than they compared pharmacokinetic characteristics of five different diseases and found out that there are profound differences between autoimmune and hematological diseases ( 57 ). Generally, RTX (as well as other MABs) pharmacokinetic is best described by means of a two compartmental model with a central plasmatic compartment and a peripheral tissue compartment with the occurrence of elimination in the central or both of these compartments ( 10 , 11 , 58 , 59 ). During the treatment of most autoimmune diseases RTX has relatively stable half-life whereas its half-life in hematologic diseases typically prolongs during the treatment as the excessive number of target cells decrease ( 60 ).…”
Section: The Pharmacokinetics Of Rituximab and The Covariates That In...mentioning
confidence: 99%
See 1 more Smart Citation